Pemberdayaan Remaja Melalui Kelompok Program Generasi Berencana Peduli Organ Reproduksi Perempuan (GEnRE POP) - Lisda Widianti Longgupa; Nurfatimah Nurfatimah; Kadar Ramadhan; Dewi Nurviana Suharto (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
The Generasi Berencana Peduli Organ Reproduksi Perempuan (GEnRE POP) program aims to empower adolescents and improve their knowledge of reproductive health. The program was implemented in Bukit Bambu Village, Poso District, involving 20 adolescents aged 15–19 years. Activities included an initial survey, interactive health education, peer facilitator training, establishment of a support group, and evaluation using pre- and post-tests. Results showed a substantial improvement in participants’ knowledge, with average scores increasing from 45 to 85 (88.9%). The program also succeeded in forming a youth reproductive health support group and enhancing participants’ communication skills through peer educator training. This participatory approach created an inclusive learning environment that encouraged adolescents to become change agents in promoting reproductive health within their community. Overall, the GEnRE POP program proved effective in increasing adolescent reproductive health literacy and is recommended for continued implementation with support from local government, health workers, and educational institutions.